Klebsiella pneumoniae bloodstream infections in hospitalised children at Red Cross War Memorial Children's Hospital : 2006 - 2011 - Buys, Heloise (Department of Paediatrics and Child Health, 2016)
Background: Klebsiella pneumoniae (KP) is a significant paediatric bloodstream pathogen in children. There is little data about KP in South African children. The focus for the present study was to address this knowledge gap. Methods: This study addressed a retrospective case notes review on bloodstream Klebsiella pneumoniae infections at a children's hospital in Cape Town, South Africa 2006-2011 using conventional descriptive and comparative statistical methods. Results: Of 410 hospitalised children with laboratory confirmed KP bloodstream infection (KPBSI), 339 (83%) were presumed extended-spectrum β-lactamase (ESBL) producing isolates. The median age (interquartile range, IQR) was 5.0 (2-16) months, 212 (51.7%) were male, 82 (20%) were HIV-infected, and 241 (58.8%) were moderately or severely underweight. The infection was nosocomial or healthcare-associated in 389 (95%) children and community-acquired in 21 (5%) children. Significant risk factors for the acquisition of ESBL-KP bloodstream infection included cephalosporin exposure in the preceding 12 months prior to the KPBSI p=<0.0001: aRR 1.25 (95% CI: 1.15-1.36); and those who had intravenous infusions for more than 3 days prior to the KPBSI, p=0.004: aRR 1.18 (95% CI: 1.05-1.31).